Staff retention in an information management environment - Odendaal, Wanda (My University, 2011)
Organisations are starting to think and operate more strategically and are beginning to realise that their survival depends on information. Information management relates to management activities concerning information. Information and the supporting systems are important business assets for establishing and leveraging information-based resources and competence, which allow organisations to compete and survive in the current competitive economic markets. In order for the information management department to support business optimally, they need to retain existing talented people who have the essential knowledge, expertise and competencies to do the work. Adding to this is the need to make the job environment more attractive to current and future job applicants. In order to do this, the management team of the information management department need to understand why people behave as they do. They must have the ability to control, direct and change behaviour, as well as be able to use the right motivation to make the job environment within the information management department more attractive. The purpose of this study is to examine staff retention in an information management environment. The literature study explores the theoretical framework of staff retention, motivation and job satisfaction. A quantitative research approach was followed and a questionnaire was used to elicit data from 50 employees working in an information management department of a petrochemical organisation. The questionnaire was used to measure employee job satisfaction levels and to identify job satisfaction factors. The findings reveal that communication, good working conditions, job security, opportunities for learning and growth, and recognition are seen in this order as being the most important job satisfaction factors. It is clear that employee expectations for job satisfaction are not met in the areas of recognition and good supervision/leadership. In addition, it is noted that employee expectations for job satisfaction are only partially met in the areas of communication, opportunities for learning and growth, promotional opportunities and compensation/pay. The value of this research is that it makes a useful contribution to the current knowledge of the management team in the information management department. The research information collected through this study can be used to establish the optimal mix of motivating factors in order to ensure that current employees are retained and that a sought-after working environment for new appointments is created.
Thesis (M. Tech. Business Administration, Faculty of Management Sciences--(Vaal University of Technology, 2010)).
Keywords: Staff retention; Information management; Petrochemical organisation - Staff retention; Job satisfaction; Employee retention; Motivation theories; Working conditions; 658.3; Personnel management; Employee retention; Job satisfaction